Investigation and Design of Auto-Part Container Leasing Platform in Information Management Framework - Patchaiappan, Patchaiappan; G. Rengamani, G. Rengamani (International Journal of Supply Chain Management, 2018)
In enterprises the Container Leasing and its application compresses the momentum circumstance of research. For Container renting stage the holder administration concentrates on process and planning of a new business. The shaping of rebuild <technique delivery anticipate discharge container is appeared in detail. Considering the element of vehicle part holder in business the data administration frameworks architecture and capacity modules are planned.